Sosialisasi Stunting di Daerah Guo Kelurahan Kuranji Kecamatan Kota Padang - Dewi Yudiana Shinta; Melly Siska Suryani; Herix Sonata MS (CANANG: Jurnal Pengabdian Masyarakat, 2024)
Stunting is a disorder child growth and development, usually caused by chronic malnutrition during early growth. Children who are stunted generally look physically proportional, but when compared to other children their age, they will look shorter or stunted. In Guo Mandiri Posyandu (Integrated Health Post for Child Health) Kuranji Padang, there are still children who are stunted, which on average is caused by helminthiasis due to poor environmental sanitation and lack of parenting knowledge. A diagnosis of stunting is made when a child's growth and development is below the standard growth curve set by WHO. This condition is caused by a prolonged lack of nutritional intake and recurrent infections, and both of these factors are influenced by inadequate parenting. Children who suffer from stunting not only experience physical limitations, but are also at risk of decreased intelligence levels, speech disorders, learning difficulties, and have a weak immune system that is vulnerable to viral and bacterial infections. The results achieved in this socialization activity are: the definition and characteristics of stunting, impacts, and efforts made in preventing stunting itself. Through a participatory approach and support from various parties, the sustainability of this socialization is expected to become a work program for the region in community-based stunting reduction. In this activity, there was an increase in residents' high knowledge by 37.2%, knowledge increased before and after the test